Recognizing Students' Characteristics in Implementing Differentiated Learning at SMKN 10 Jeneponto - Nurkaidah, Nurkaidah; Sunra, La; Sofyan , Ryan Rayhana (Tamaddun Life, 2025)
This research explores how English teachers at SMKN 10 Jeneponto identify student characteristics in the implementation of differentiated learning, which is aligned with the “Merdeka” curriculum. This research uses mixed methods that combine qualitative and quantitative research. In collecting data, the researchers conducted interviews, questionnaires, and documentation. Three English teachers participated as subjects in this research. The findings show that teachers use questionnaires administered by counseling teachers and follow-up interviews to detect students' learning styles, such as visual, auditory, or kinesthetic. From the results of the questionnaire analyzed by the researchers, it was found that 58.33% of students with visual learning style, 37.5% auditory, and 4.17% visual-auditory. After the questionnaire from the counseling teacher, the subject teachers also conducted follow-up interviews to find out more about students' learning styles and abilities. In identifying students' abilities, teachers also rely on observations during the learning process and targeted questions at the beginning of the lesson. This method allows teachers to adjust their instructional strategies to meet students' needs more effectively. The research concludes that combining interviews and questionnaires provides a comprehensive approach to understanding students' learning styles and abilities, which contributes to the successful implementation of differentiated learning. This approach increases student engagement, supports individual learning preferences, and ultimately improves learning outcomes.